An extraoral approach to intraoral cooling-a feasibility study in non-cancer patients - L. Najaf; N. Borgvall; K. Vennman; J. Walladbegi (BMC, 2023)
Abstract Background Cryotherapy, using ice chips (IC) is an effective strategy to prevent chemotherapy-induced oral mucositis (OM) in selected cancer patient cohorts. However, although effective, use of IC may cause adverse reactions, e.g., nausea, numbness, and shooting pain in the teeth, which could have an adverse impact on the medical treatment. Furthermore, IC requires water of good quality to minimize risk of serious systemic infections. To eliminate these disadvantages, novel cooling devices have emerged as alternative cooling modalities. Thus, the aim was to evaluate the efficacy and tolerability profile of extraoral cooling for intraoral temperature reduction. Subjects and Methods This experimental pilot study was conducted at the Institute of Odontology, The Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden. In total, six healthy volunteers were enrolled in this study. At baseline and following 30-, and 60 min of cooling with the extraoral cooling device, intraoral mucosal temperatures were measured using a thermographic camera, and a questionnaire related to tolerability was completed. Results Following 30-, and 60 min of cooling, the intraoral temperature decreased with 2.0 °C and 2.3 °C, respectively. Extraoral cooling was well tolerated, and all subjects endured the entire cooling session of 60 min. Conclusion Extraoral cooling reduces intraoral mucosal temperatures and is a well-tolerated cooling modality.